(3EbJUGO GdUMGaI GdecJhHI aj GdLRGFQ (B/s - (3afj, YGThQs ((3GdLRGFQ(B-(3GdQhjHI (B:s (3GdeDSSI GdhWfjI ddEJUGd h GdfTQ h GdETgGQ ,s, 2013)
(3LedI ef GdGYJHGQGJ LYdJfG ffXQ ddUMGaI GdecJhHI aj GdLRGFQ ef RGhjI GbJUGOjI HMKI RGhjI GbJUGOjI cdjI JfXQ ddfTGW h JWhQg aj NVe GdJMhdGJ GdGLJeGYjI h GdSjGSjI GdJGQjNjI efP GdGSJbdGd h NdGd aJQI GdGUdGMGJ h GeJOGOGJgG aj GdhGbY GdQGgf hUhdG Gdi GSTQGa GdeSJbHd GdbQjH aj Xd JMhdGJ YGdejI TedJ bWGY GdEYdGe HQeJg(B. (3h TedJ GjVG GdfXQjI GdGbJUGOjI faSgG h bO eKd XghQ bGfhf GdGYdGe dSfI (B1990(3fbWI JMhd LPQj aj GdJGQjN GdGbJUGOj dhSGFd GdGYdGe h dGSjeG GdUMGaI GdecJhHI aj GdLRGQ abO JMhdJ TQhW GdOQGSI GdGbJUGOjI HTcd LPQj dbO JQJH Yf Pdc bGfhf GfJgGA eQMdI GdGTcGdI GdGOGQjI h GdSjGSI ddUMGaI GdecJhHI h HOGjI fhY LOjO ef GdGTcGdjGJ GdGbJUGOjIs
Keywords: (3GbJUGO GdUMGaI GdecJhHIs; (3GdUMGaI GdecJhHIs